2012
DOI: 10.1002/jssc.201200349
|View full text |Cite
|
Sign up to set email alerts
|

Determination of cyflumetofen residue in water, soil, and fruits by modified quick, easy, cheap, effective, rugged, and safe method coupled to gas chromatography/tandem mass spectrometry

Abstract: A new, highly sensitive, and selective method was developed for the determination of the cyflumetofen residue in water, soil, and fruits by using gas chromatography quadruple mass spectrometry. The target compound was extracted using acetonitrile and then cleaned up using dispersive solid-phase extraction with primary and secondary amine and graphitized carbon black, and optionally by a freezing-out cleanup step. The matrix-matched standards gave satisfactory recoveries and relative standard deviation values i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…HPLC was used to test the metabolism of acaricides by recombinant CYP389C16 in vitro . Only cyflumetofen showed a slight self‐decomposition (7.8 ± 1.1%) after 2 h incubation in the reaction, which was due to the instability of cyflumetofen in the aqueous phase . Recombinant CYP389C16 could metabolize cyflumetofen and pyridaben, and the rates were 14.3 ± 1.2% and 25.0 ± 0.7% for cyflumetofen, and 27.6 ± 1.9% and 39.7 ± 1.0% for pyridaben when incubated with 20 and 40 pmol of recombinant proteins, respectively (Table ).…”
Section: Resultsmentioning
confidence: 86%
“…HPLC was used to test the metabolism of acaricides by recombinant CYP389C16 in vitro . Only cyflumetofen showed a slight self‐decomposition (7.8 ± 1.1%) after 2 h incubation in the reaction, which was due to the instability of cyflumetofen in the aqueous phase . Recombinant CYP389C16 could metabolize cyflumetofen and pyridaben, and the rates were 14.3 ± 1.2% and 25.0 ± 0.7% for cyflumetofen, and 27.6 ± 1.9% and 39.7 ± 1.0% for pyridaben when incubated with 20 and 40 pmol of recombinant proteins, respectively (Table ).…”
Section: Resultsmentioning
confidence: 86%
“…The method with modification/s 1 alone, 1 + 2, 1 + 2 + 3 and 1 + 2 + 3 + 4 yielded 61, 68, 104 and 108% mean recoveries of pesticides, respectively. However, Li et al [25] reported acceptable range of recoveries (83.9-97.9%) of cyflumetofen residues from soil by adopting the original QuEChERS method. They could recover adequate volume of supernatant for d-SPE cleanup with PSA after extraction with 10 mL of acetonitrile for 10 g of soil matrix.…”
Section: Methods Validationmentioning
confidence: 99%
“…Cyflumetofen and samples were separated by an isocratic program 80% A: 20% B (A: methanol, B: 0.1% acetic acid in water) with a flow rate of 0.8 mL min −1 at 35 ∘ C. Cyflumetofen elution was monitored by changes in absorbance at 210 and 230 nm. Because cyflumetofen is unstable in aqueous phase (self-decomposition), 28 thus there were two controls (CK1: recombinant protein +10 mg L −1 cyflumetofen for 0 h and CK2: without recombinant protein +10 mg L −1 cyflumetofen for 1 h, respectively) in this study to eliminate the interference of its self-decomposition. A standard curve was built by taking the gradient concentration of standard cyflumetofen as abscissa, and the value of peak area as ordinate.…”
Section: Decomposition Of Cyflumetofen By Recombinant Tcgstm02mentioning
confidence: 99%